1999
DOI: 10.1152/jn.1999.82.2.946
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Dependent Inactivation of High-Threshold Ca2+ Currents in Hippocampal Granule Cells of Patients With Chronic Temporal Lobe Epilepsy

Abstract: Intracellular Ca(2+) represents an important trigger for various second-messenger mediated effects. Therefore a stringent control of the intracellular Ca(2+) concentration is necessary to avoid excessive activation of Ca(2+)-dependent processes. Ca(2+)-dependent inactivation of voltage-dependent calcium currents (VCCs) represents an important negative feedback mechanism to limit the influx of Ca(2+) that has been shown to be altered in the kindling model of epilepsy. We therefore investigated the Ca(2+)-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
17
0
2
Order By: Relevance
“…6 Satyanarayana et al, also reported decrease in duration of THLE in MES model with amlodipine pretreatment in graded doses (1mg/kg, 2mg/kg, 4mg/kg) and also observed delay in the onset of clonic convulsions in PTZ model with similar pretreatments. 4 Results of present study are comparable to this study. 9 Jagathi devi et al, showed the combination of amlodipine and indomethacin showed a superior anticonvulsant effect than the use of Amlodipine alone, in both electrically and chemically induced seizures with picrotoxin in mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…6 Satyanarayana et al, also reported decrease in duration of THLE in MES model with amlodipine pretreatment in graded doses (1mg/kg, 2mg/kg, 4mg/kg) and also observed delay in the onset of clonic convulsions in PTZ model with similar pretreatments. 4 Results of present study are comparable to this study. 9 Jagathi devi et al, showed the combination of amlodipine and indomethacin showed a superior anticonvulsant effect than the use of Amlodipine alone, in both electrically and chemically induced seizures with picrotoxin in mice.…”
Section: Discussionsupporting
confidence: 88%
“…3 A fall in the extracellular calcium concentrations occurs prior to onset of seizure activity followed by an increase in the intracellular calcium concentrations. 4 Amlodipine belongs to the 1,4-dihydropyridine (DHP) group of CCBs. Amlodipine exhibits unique features that afford a smooth gradual onset of action and sustained effect that provides for continuous and consistent activity throughout a 24-hour period.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, involvement of the cytoskeleton has been found in cardiac myocytes [34], hippocampal cells [4,30] and snail neurons [23,29] and calmodulin has been identified as the Ca 2+ sensor for CDI of L-type and P/Q-type Ca 2+ channels in expression systems [35,53,55,65], whereby these channels are regulated by calmodulin in a lobespecific manner [39]. To fulfil this function Ca 2+ -free calmodulin and L-type Ca 2+ channels are preassociated as has been shown by fluorescence resonance energy transfer (FRET) two-hybrid mapping [20].…”
Section: Introductionmentioning
confidence: 99%
“…One hippocampus was immediately frozen in liquid nitrogen for in situ hybridization, whereas the contralateral hippocampus was used for preparation of 400-m transverse vibratome slices. From these slices, single CA1 neurons were harvested with a glass pipette in less than 10 l of extracellular solution (Beck et al, 1999). mRNA was isolated using the Dynabead mRNA Direct Micro Kit (Dynal, Hamburg, Germany) according to the manufacturer's protocol.…”
mentioning
confidence: 99%